Social Policy in Social Work Education and Practice - Innovative Approaches - Sarah P. Lonbay; Marija Stambolieva (Social Work & Society, 2022)
This Special Issue is interested in the educational context of social policy and its implications for social work professionals and community practice. The papers presented here were selected based on an open call for contributions. They examine the role of social policy within the context of social work education and its relationship to actual experiences of professional practice. Additionally, they explore the debates around social workers as 'policy actors', with a focus on how social work educators train or educate social work students to influence social policy. The Issue offers an international perspective with contributions from the UK, Germany, Estonia, Italy, USA, and Norway.